Renal complications of sickle cell disease - Sharpe, Claire (Henry Stewart Talks, 2016)
The underlying pathophysiology of sickle cell nephropathy, The common clinical manifestations of the disease, Early screening and management, Management of advanced chronic kidney disease due to sickle cell nephropathy, Outcomes following kidney transplantation in patients with sickle cell disease